2016
DOI: 10.1063/1.4961460
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and nucleation in multilayer growth of PTCDI-C8 studied with in situ X-ray growth oscillations and real-time small angle X-ray scattering

Abstract: We study nucleation and multilayer growth of the perylene derivative PTCDI-C and find a persistent layer-by-layer growth, transformation of island shapes, and an enhancement of molecular diffusivity in upper monolayers (MLs). These findings result from the evaluation of the ML-dependent island densities, obtained by in situ real-time grazing incidence small angle X-ray scattering measurements and simultaneous X-ray growth oscillations. Complementary ex situ atomic force microscopy snapshots of different growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…They involve films of water (Gutfreund et al, 2016), alkane (Fontaine et al, 2018), lipid (Nylander et al, 2017), organic semiconductor (Zykov et al, 2017) and inorganic semiconductor (Highland et al, 2017;Singh et al, 2017); microgels (Kyrey et al, 2018) and microemulsions ; templated (Li-Destri et al, 2016) and self-assembled polymer structures (Berezkin et al, 2018;Glavic et al, 2018;Xie et al, 2018); nanocolumns growing from vapor deposition (Haddad et al, 2016); Au nanoparticles during CO oxidation (Odarchenko et al, 2018); C 60 monolayer islands (Kowarik, 2017); magnetic nanoparticles (Ukleev et al, 2016(Ukleev et al, , 2017 and magnetic films (Merkel et al, 2015;Glavic et al, 2018); lithographic gratings (Pflü ger et al, 2019); and sputtered multilayers . They involve films of water (Gutfreund et al, 2016), alkane (Fontaine et al, 2018), lipid (Nylander et al, 2017), organic semiconductor (Zykov et al, 2017) and inorganic semiconductor (Highland et al, 2017;Singh et al, 2017); microgels (Kyrey et al, 2018) and microemulsions ; templated (Li-Destri et al, 2016) and self-assembled polymer structures (Berezkin et al, 2018;Glavic et al, 2018;Xie et al, 2018); nanocolumns growing from vapor deposition (Haddad et al, 2016); Au nanoparticles during CO oxidation (Odarchenko et al, 2018); C 60 monolayer islands (Kowarik, 2017); magnetic nanoparticles (Ukleev et al, 2016(Ukleev et al, , 2017 and magnetic films (Merkel et al, 2015;…”
Section: Published Usagementioning
confidence: 99%
“…They involve films of water (Gutfreund et al, 2016), alkane (Fontaine et al, 2018), lipid (Nylander et al, 2017), organic semiconductor (Zykov et al, 2017) and inorganic semiconductor (Highland et al, 2017;Singh et al, 2017); microgels (Kyrey et al, 2018) and microemulsions ; templated (Li-Destri et al, 2016) and self-assembled polymer structures (Berezkin et al, 2018;Glavic et al, 2018;Xie et al, 2018); nanocolumns growing from vapor deposition (Haddad et al, 2016); Au nanoparticles during CO oxidation (Odarchenko et al, 2018); C 60 monolayer islands (Kowarik, 2017); magnetic nanoparticles (Ukleev et al, 2016(Ukleev et al, , 2017 and magnetic films (Merkel et al, 2015;Glavic et al, 2018); lithographic gratings (Pflü ger et al, 2019); and sputtered multilayers . They involve films of water (Gutfreund et al, 2016), alkane (Fontaine et al, 2018), lipid (Nylander et al, 2017), organic semiconductor (Zykov et al, 2017) and inorganic semiconductor (Highland et al, 2017;Singh et al, 2017); microgels (Kyrey et al, 2018) and microemulsions ; templated (Li-Destri et al, 2016) and self-assembled polymer structures (Berezkin et al, 2018;Glavic et al, 2018;Xie et al, 2018); nanocolumns growing from vapor deposition (Haddad et al, 2016); Au nanoparticles during CO oxidation (Odarchenko et al, 2018); C 60 monolayer islands (Kowarik, 2017); magnetic nanoparticles (Ukleev et al, 2016(Ukleev et al, , 2017 and magnetic films (Merkel et al, 2015;…”
Section: Published Usagementioning
confidence: 99%
“…[ 8–12 ] The ability to tune the PEM's architecture with nanometer precision is very promising aspect for using them in biomedical applications. Understanding the molecular dynamics of the participating species, either in situ [ 13–21 ] or ex situ, [ 22–26 ] is useful to further tune the PEM architecture for specific applications. When it comes to bio‐sensing and drug‐delivery applications, the bulk properties of PEM films play a significant role in their optimal functionality.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that step edges of flexible alkyl chains support the diffusion between the different terrace levels, as shown by a comparative study of pentacene and alkylperylene-tetracarboxylic diimides. 44,45 The smooth film surface at large film thicknesses has clear effects on the XRR investigations of the 13 nm and 99 nm films: film thickness oscillations (Kiessig fringes) are observed close to the angle of total external reflection (Fig. 4b and c).…”
Section: Discussionmentioning
confidence: 93%